2016
DOI: 10.1038/eye.2016.88
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of botulinum toxin-A injection in lacrimal gland and conjunctivodacryocystorhinostomy for treatment of epiphora due to proximal lacrimal system obstruction

Abstract: Purpose To investigate and compare the efficacy of botulinum toxin-A injection in the lacrimal gland and conjunctivodacryocystorhinostomy surgery for the treatment of epiphora caused by proximal lacrimal system obstruction. Methods Charts of the patients with proximal canalicular obstruction who had undergone conjunctivodacryocystorhinostomy with permanent tube insertion (18 patients, group 1) or 4 units of botulinum toxin-A injection in the palpebral lobe of the lacrimal gland (20 patients, group 2) were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 29 publications
(116 reference statements)
1
32
0
Order By: Relevance
“…Ziahosseini et al [7] evaluated the effect of BTA injection for epiphora by the reduction of the mean Munk score after injection from 3.4 to 1.6 in the series with 22 eyes. Kaynak et al [8] reported both qualitative and quantitative evaluations of epiphora in a comparative study including 20 eyes treated with BTA injection: the mean Munk and Schirmer-1 scores were 3.95 and 12 mm before injection respectively, and decreased to 1.05 and 5.4 mm at 1 month after injection and to 1.36 mm and 5.8 mm at 3 months after injection, respectively. These results of previous studies were similar to our findings showing significant improvement of epiphora at 1 month and 3 months after BTA injection [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziahosseini et al [7] evaluated the effect of BTA injection for epiphora by the reduction of the mean Munk score after injection from 3.4 to 1.6 in the series with 22 eyes. Kaynak et al [8] reported both qualitative and quantitative evaluations of epiphora in a comparative study including 20 eyes treated with BTA injection: the mean Munk and Schirmer-1 scores were 3.95 and 12 mm before injection respectively, and decreased to 1.05 and 5.4 mm at 1 month after injection and to 1.36 mm and 5.8 mm at 3 months after injection, respectively. These results of previous studies were similar to our findings showing significant improvement of epiphora at 1 month and 3 months after BTA injection [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports described the effects of injection of botulinum toxin-A (BTA) in the lacrimal gland in patients with epiphora [3][4][5][6][7][8]. BTA injection in the lacrimal gland decreases tear production by blocking presynaptic release of acetylcholine into the neuromuscular end plates of cholinergic nerve fibres [9].…”
Section: Introductionsmentioning
confidence: 99%
“…Lacrimal gland botulinum toxin A (BTA) injections successfully alleviate epiphora with documented improvement in Munk scores. [ 1 2 3 ] The toxin inhibits release of acetylcholine in all parasympathetic and cholinergic postganglionic sympathetic neurons, resulting in reduced tear secretion. [ 4 ] Injections are generally well tolerated and the side effects reported after this procedure are transient ptosis (7–25%) and diplopia (7%) in a few cases.…”
mentioning
confidence: 99%
“…28,29 This is a less invasive procedure and requires less expertise. A transconjunctival approach is preferred.…”
mentioning
confidence: 99%